Under Western Eyes - Conrad, Joseph, 1857-1924 (Salt Lake City, UT : Project Gutenberg, 2006)
"Under Western Eyes" by Joseph Conrad is a novel published in 1911. Set in St. Petersburg and Geneva, it follows Razumov, a solitary Russian student whose carefully planned future unravels when a fellow student involves him in a political assassination. Forced to make an impossible choice between betrayal and survival, Razumov becomes entangled with revolutionaries and the victim's idealistic sister. Conrad's cynical exploration of revolutionary idealism, autocratic power, and moral isolation stands as his response to Dostoevsky and his own conflicted past. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Under_Western_Eyes_(novel)
Release date is 2006-01-09
Produced by An Anonymous Volunteer and David Widger
Keywords: Political fiction; Bombings -- Fiction; Saint Petersburg (Russia) -- Fiction; College students -- Fiction; Russia -- History -- 1904-1914 -- Fiction; Terrorism -- Fiction; Geneva (Switzerland) -- Fiction